2004
DOI: 10.1016/j.febslet.2004.09.081
|View full text |Cite
|
Sign up to set email alerts
|

A novel site of AKT‐mediated phosphorylation in the human MDM2 onco‐protein

Abstract: MDM2 is an E3 ubiquitin ligase which mediates ubiquitylation and proteasome-dependent degradation of the p53 tumor suppressor protein. Phosphorylation of MDM2 by the protein kinase AKT is thought to regulate MDM2 function in response to survival signals, but there has been uncertainty concerning the identity of the sites phosphorylated by AKT. In the present study, we identify Ser-166, a site previously reported as an AKT target, and Ser-188, a novel site which is the major site of phosphorylation of MDM2 by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 21 publications
6
42
0
1
Order By: Relevance
“…We found that increasing AF concentrations increase Mdm2 ubiquitylation and degradation by the proteasome (Figures 2 and 3), which is consistent with a recent study (Stommel and Wahl, 2004). We also found that under these conditions, there is a reduction of Akt-mediated Mdm2 phosphorylation at serine 166 (Figure 4a), phosphorylation that stabilizes Mdm2 (Feng et al, 2004;Milne et al, 2004). Accordingly, Akt activity (measured as phosphorylation at serine 473) tended to be attenuated with increasing AF concentrations (Figure 4a).…”
Section: Discussionsupporting
confidence: 80%
“…We found that increasing AF concentrations increase Mdm2 ubiquitylation and degradation by the proteasome (Figures 2 and 3), which is consistent with a recent study (Stommel and Wahl, 2004). We also found that under these conditions, there is a reduction of Akt-mediated Mdm2 phosphorylation at serine 166 (Figure 4a), phosphorylation that stabilizes Mdm2 (Feng et al, 2004;Milne et al, 2004). Accordingly, Akt activity (measured as phosphorylation at serine 473) tended to be attenuated with increasing AF concentrations (Figure 4a).…”
Section: Discussionsupporting
confidence: 80%
“…Although p53 facilitates FLIP downregulation (Fukazawa et al, 2001) and p53 level and function could be correlated with FLIP downregulation in response to various cellular stimuli (Fukazawa et al, 2001;Chandrasekaran et al, 2006), this report provides the first direct evidence for a role of p53 in FLIP degradation. Indeed, Akt has been shown to upregulate FLIP content (Panka et al, 2001;Suhara et al, 2001;Nam et al, 2002Nam et al, , 2003Skurk et al, 2004;Alladina et al, 2005;Sta¨rck et al, 2005;Moriyama and Yonehara 2007;Moumen et al, 2007;Shim et al, 2007) and/or to alter p53 content by activating MDM2 (Mayo and Donner 2001;Zhou et al, 2001;Milne et al, 2004). Our results provide strong evidence that Akt may have a wide-ranging anti-apoptotic role, which includes interfering with the FLIP-p53 binding and FLIP ubiquitination.…”
Section: Discussionsupporting
confidence: 55%
“…Although the precise molecular mechanism responsible for the TWIST-induced Akt activation is not clear, recently, a possible link between TWIST and Akt pathway has been suggested. For example, Akt has been shown to interferer with p53/MDM2 pathway, 27,28 which is also a target of TWIST. 7 In addition, it was reported that inactivation of STAT3 in a breast cancer cell line, 4T1, led to downregulation of Akt-phosphorylation which was associated with completely abolished TWIST protein expression.…”
Section: Discussionmentioning
confidence: 99%